Celebration of the Young Adult’s Body in Salinger’s The Catcher in the Rye - Thapa, Hukum (Mindscape: A Journal of English & Cultural Studies, 2023)
This paper studies the celebration of young adult’s body in J.D. Salinger’s The Catcher in the Rye. It analyzes why and how the young adult protagonist Holden Renaultin in The Catcher in the Rye celebrates the body since the young adults perceive their bodies as the means of power, change, conflict and solution. It argues that young adults like Holden celebrate their bodies to establish their identity, freedom and to demonstrate their maturity. They also exhibit their individuality through their celebration of the body. They desire to be noticeable and different from others by means of the body celebration. This paper contends that young adults celebrate their bodies by means of exercise, wearing different types of clothes, playing and dancing. For the analytical purpose, it basically engages with the critical insights of Judith Butler, Elinor Fuchs, Rush Rehm, Michel Foucault and Clinton Sanders et al. Finally, the study expects to open up a new approach in the study of body celebration of young adults and its consequences.